Creating behavioral engagement among higher education’s prospective students through social media marketing activities: The role of brand equity as mediator - Ruangkanjanases, Athapol; Sivarak, Ornlatcha; Wibowo, Ardy; Chen, Shih-Chih (Frontiers in Psychology, 2022)
In today's competitive environment, higher education needs to find an effective way to convey its brand to prospective students. Given that the “digital native” (Gen Z) is becoming college aged, social media marketing has become an essential approach to engage with them. However, blasting out recruiting content on its social feeds just isn't working. By developing the higher education adjusted SMMA, structural equation modeling was adopted to figure out its effects on higher education brand equity and prospective student behavioral engagement, quantitatively. 356 3rd grade high school students in Indonesia were employed to assess the structural model. According to the findings of this study, SMMA has a considerable influence on brand equity and behavioral engagement, and brand equity has a noteworthy effect on behavioral engagement. Moreover, brand equity was found as a statistically meaningful mediator in the relationship between SMMA and behavioral engagement. The outcome advised the higher education need to organize its social in fun and interactive ways by leveraging higher education’s SMMA as a pillar or benchmark on arranging social media posts and content. Yet, the content and posts should still need prioritize institution awareness and the good image of a higher education. The theoretical and managerial implication were discussed further.